Evaluating UKM's linear algebra final questions in line with outcome based education using bloom's taxonomy and item analysis - Fatimah Abdul Razak,; Syahida Che Dzul-Kifli,; Abdul Ghafur Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Crafting exam questions is an art in itself. Even though there is no strict formula for producing perfect exam questions, the current line of thinking points in the direction of Outcome Based Education (OBE). In this study, we evaluate the final exam questions of the 2012 Linear Algebra course using OBE standards in two separate phases. Firstly, the questions are categorised according to the Course Learning Objectives (CLO) and evaluated in light of the six cognitive domains of Bloom’s taxonomy. This first phase aims to assess whether the examination paper has the right balance of questions in each domain. The second phase involves analysing the results of the students in the same examination using item analysis techniques. The analysis includes finding the discrimination index and difficulty index derived from the answers of the students. This second phase focuses on determining the effectiveness of the questions in discriminating students according to their grasp of the CLO. Based on the results, some improvements are suggested. We conclude that except for the analysis level, the cognitive levels of all the questions are generally acceptable.